2021
DOI: 10.1111/ijcp.14475
|View full text |Cite
|
Sign up to set email alerts
|

Management of urinary tract infections and antibiotic susceptibility patterns of bacterial isolates

Abstract: Aim of study: Urinary tract infections (UTIs) are among the most common infections affecting individuals of different ages worldwide. Antimicrobial agents are usually the first-line treatment for UTIs, and the use of the prescribed antibiotic is escalating, resulting in increased rates of bacterial resistance and UTI recurrence. The current study aimed to identify the causative bacteria in Jordan, to explore their resistance pattern to antibiotics and to describe drug-related problems (DRPs) associated with UT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Again, these UTI isolates exhibited multidrug resistance. The fluoroquinolone antibiotics have been used for the treatment of resistant E. coli in uncomplicated UTIs as a first-line drug in communities that have reported 10-20% resistance to TMP-SMX [60]. However, several studies have reported resistance to ciprofloxacin and ofloxacin [61].…”
Section: Discussionmentioning
confidence: 99%
“…Again, these UTI isolates exhibited multidrug resistance. The fluoroquinolone antibiotics have been used for the treatment of resistant E. coli in uncomplicated UTIs as a first-line drug in communities that have reported 10-20% resistance to TMP-SMX [60]. However, several studies have reported resistance to ciprofloxacin and ofloxacin [61].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, there are many of data about the level of resistance to different antibiotics. Despite on definitive success of antibiotic therapy for the treatment of UTI, antimicrobial resistance remains a main public health problem in the world [14,15]. Among different multidrug-resistant microorganisms (MDM), E. coli is the most common causative pathogen associated with UTI, followed by Klebsiella spp, Enterococcus spp, and other gram-negative bacteria.…”
Section: The Current Level Of Resistance To Different Antibiotics For...mentioning
confidence: 99%
“…According to the Infectious Diseases Society of America (IDSA), urinary tract infections (UTIs) are defined as the association of significant bacteriuria, leukocyturia and suggestive clinical symptoms (Nicolle et al, 2019). UTIs are common reasons for consultation in general practice and emergency departments (Amawi et al, 2021). Approximately 150 million UTI episodes are registered yearly worldwide (Stamm and Norrby, 2001).…”
Section: Introductionmentioning
confidence: 99%